The phenomenon of antibiotic resistance and people's knowledge (One Health & Risk Management, 2023)
Introduction. Antibiotic resistance occurs when bacteria evolve to resist the effects of antibiotics that were previously effective in treating bacterial infections. This can happen when antibiotics are overused or misused, as well as in other situations where bacteria are exposed to antibiotics over a long period of time. Antibiotic resistance is a major global health concern, as it can lead to infections that are difficult or impossible to treat, causing prolonged illness, disability, and death.Aim. Studying the level of knowledge of the population with reference to the phenomenon of antibiotic resistance.Material and methods. For this study, open access international information resources were analyzed using PubMed, Hinari, Google Scholar databases. The search was conducted using key words in English and Romanian: "antibiotic resistance", "KAP population", "antimicrobials". Reference period – the last ten years.Rezults. Antimicrobial resistance (AMR) is a growing global health threat that has been recognized as one of the most urgent challenges facing public health today.Antibiotics are a type of antimicrobial drug used to treat bacterial infections. So, people in the world know antibiotics are one of the most commonly prescribed classes of drugs worldwide. They are used to treat a wide range of bacterial infections, including pneumonia, tuberculosis, and urinary tract infections. It is known that overuse and misuse of antibiotics is a major problem around the world. This can lead to the development of antibiotic-resistant bacteria, which can make it more difficult to treat infections and increase the risk of serious complications. In some interviews, people answered that antibiotic resistance is a growing global health threat that has been recognized as one of the most urgent challenges facing public health today. It can lead to a prolonged illness, disability, and death, and it has the potential to render many of our current antibiotic treatments ineffective. The same people know that antibiotics are also widely used in agriculture, particularly in animal agriculture. This can contribute to the development of antibiotic-resistant bacteria and increase the risk of transmission to humans. Although, the development of new antibiotics has been slow in recent years due to a range of factors, including the high cost and lengthy development process. However, there is a need for new antibiotics to combat the rising problem of antibiotic-resistant bacteria. It is worth noting that people's knowledge and attitudes towards antibiotic resistance in low- and middle-income countries can vary depending on a number of factors, including levels of education, awareness, and access to healthcare. However, in general, there is growing recognition of the problem of antibiotic resistance in low- and middle-income countries, and efforts are being made to raise awareness and address the issue.Conclusions. In general, raising awareness and educating the public about antibiotic resistance is important in order to help prevent the spread of resistant bacteria and ensure that antibiotics remain effective for future generations.Notă. The study was carried out with the financial support of the European multinational project: "Phage treatment and wetland technology as intervention strategy to prevent dissemination of antibiotic resistance in surface waters (PhageLand)", number: 22.80013.8007.1M.